PEMANFAATAN CRM (CUSTOMER RELATIONSHIP MANAGEMENT) SEBAGAI PROMOSI DAN PENGEMBANGAN PERUSAHAAN BERBASIS WEB DAN SMS - Erlan Darmawan; Galih Agustian Nurdaya (NUANSA INFORMATIKA, 2012)
Abah Madja Futsal company is a rental service company of Futsal field in  Kuningan has focused on customers’ satisfaction in accordance with its vision and mission. But in fact to realize the objective, the information services provided by the company is still not optimal, because the presentation of information that the company provides has very limited coverage, so the goal of keeping customers’ loyalty to the company is not achieved maximally. Promotion is one of the most important things in a company to market its products, there are some methods used to promote the products by company. CRM (Customer Relationship Management) helps companies to define and meet the customer by providing creative solutions to expand the relationship more than an investment. CRM provides guaranteed services that are directed by connecting the bond between loyalty of company and its customers in the long run term. The implementation of CRM can’t be separated with the use of information technology, without technology it would be very difficult to implement CRM strategies for customer interaction including the use of technologies such as email, phone, web, SMS, and others. The service is packed with information-based website creation and SMS, so the customers can obtain information easily.Keyword : CRM, Campaign, Company, WEB, SMS